Hygiene Sanitasi Pada Makanan di Angkringan 26 Ilir Kota Palembang - Maria Ulfah (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Background : Food presentation is the final series of food journey. Hygiene and foodsanitation issues are very important, especially in public places that are closely relating o services for many people such as hospitals, restaurants or restaurants and streetvendors. Objective: to determine the presence or absence of Esherichia Coli bacteriain food at Angkringan 26 Ilir, Palembang City in 2021. This study in June-July 2021. Methods: This study used laboratory testing and observation methods with 11 samples of food sold at Angkringan 26 Ilir. The results of the microbiology laboratory test of Esherichia Coli bacteria were all negative. Results: The results showed that personal hygiene did not pay attention to cleanliness in the places wherethey sell, there were 3 traders who still did not get used to washing their hands before touching food, there are 9 traders who did not wear aprons when touching food, there were 5 traders who did not use tools/hand mats when handling food. touching food, and 5 male traders serving food while smoking. From the results of observations in the clean liness of food processing places, it was found that there were 4 traders who didnot provide a clean place, and there were 4 traders who did not provide trash cans. From the results of observations of food presentation there are 7 traders who serve itcold, and there are 6 traders who serve food not in a closed state. Suggestion: Based on observations made to traders, personal hygiene needs to be improved, especially wearing an apron when handling food and getting used to washing hands so that the food to be touched is not contaminated with microbiology that can cause disease